The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1177/1352458518761187
|View full text |Cite
|
Sign up to set email alerts
|

Online meditation training for people with multiple sclerosis: A randomized controlled trial

Abstract: An online MBI could be an effective psychological treatment for the promotion of well-being in MS in short-term. However, the lack of lasting effects requires the development of new strategies to support long-term changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
119
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(120 citation statements)
references
References 28 publications
1
119
0
Order By: Relevance
“…Twelve RCTs were identified as eligible for inclusion in the systematic review. [21][22][23][24][25][26][27][28][29][30][31][32] However, only eight studies reported endpoint data that could be included in the meta-analysis. 21-24 28-30 32 (figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve RCTs were identified as eligible for inclusion in the systematic review. [21][22][23][24][25][26][27][28][29][30][31][32] However, only eight studies reported endpoint data that could be included in the meta-analysis. 21-24 28-30 32 (figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…22 23 27 28 31 32 Three studies required a personal intake interview to take part, 26 27 30 two sought baseline evidence of impaired mental well-being. 21 28 Eight studies reported session content, 21-23 25-29 three gave minimal description, [30][31][32] one referred to the study protocol. 24 Seven studies described home practices.…”
Section: Intervention Characteristicsmentioning
confidence: 99%
“…Good sleep is pivotal to maintaining a critical level of physical, mental, and emotional well-being [1,2], including optimal cognitive functioning [3]. At any given time, 50% of the general population are affected with one or more sleep problems such as difficulty in falling or staying asleep, staying awake, or adhering to a consistent sleep/wake schedule [4].…”
Section: Introductionmentioning
confidence: 99%
“…A MBI has been shown to positively influence QoL, depression, anxiety and fatigue in MS patients in an RCT (intervention vs. waiting list control group) with a sample size of 150 patients and rigorous study design (pre- and post-intervention and 6 months follow-up) (Grossman et al, 2010 ). These beneficial effects have been confirmed in other RCTs that used an active control group (psychoeducational group) (Carletto et al, 2017 ; Cavalera et al, 2018 ). Moreover, sleep problems and illness perception improved to a greater extent in the intervention group than in the control group (Carletto et al, 2017 ; Cavalera et al, 2018 ).…”
Section: Mindfulnessmentioning
confidence: 53%
“…Moreover, sleep problems and illness perception improved to a greater extent in the intervention group than in the control group (Carletto et al, 2017 ; Cavalera et al, 2018 ). While the beneficial effects lasted for 6 months after conventional MBI (Carletto et al, 2017 ), the effects could not be maintained for 6 months with online mindfulness training (Cavalera et al, 2018 ).…”
Section: Mindfulnessmentioning
confidence: 99%